Optimal management of ulnar collateral ligament injury in baseball pitchers - Hibberd, Elizabeth E (Open Access J Sports Med, 2015)
The ulnar collateral ligament stabilizes the elbow joint from valgus stress associated with the throwing motion. During baseball pitching, this ligament is subjected to tremendous stress and injury if the force on the ulnar collateral ligament during pitching exceeds the physiological limits of the ligament. Injuries to the throwing elbow in baseball pitchers result in significant time loss and typically surgical intervention. The purpose of this paper is to provide a review of current information to sports medicine clinicians on injury epidemiology, injury mechanics, injury risk factors, injury prevention, surgical interventions, nonsurgical interventions, rehabilitation, and return to play outcomes in baseball pitchers of all levels.